2019
DOI: 10.1038/s41598-019-52018-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy underweight and obesity are positively associated with small-for-gestational-age infants in a Chinese population

Abstract: The association between suboptimal pre-pregnancy body mass index (BMI) and small-for-gestational-age (SGA) infants is not well defined. We investigated the association between pre-pregnancy BMI and the risk of SGA infants in a Chinese population. We performed a cohort study among 12029 mothers with a pregnancy. This cohort consisted of pregnant women that were: normal-weight (62.02%), underweight (17.09%), overweight (17.77%) and obese (3.12%). Birth sizes were reduced in the underweight and obese groups compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
4
25
2
1
Order By: Relevance
“…This corresponds to a recent study from Finland showing that 63.8% of women born in Somalia were overweight/obese compared to 29.7% of Finnish women [30]. One study found an association between obesity (but not overweight) and higher risk for giving birth to a baby small for gestational age (RR 2.66, CI 2.01, 3.52) [31] but other studies have shown inconsistent results of the link between overweight and SGA [32]. Another possible explanation is that placenta-mediated diseases (like preeclampsia and SGA) and epigenetic factors can be transferred to the following generations [33].…”
Section: Discussionsupporting
confidence: 80%
“…This corresponds to a recent study from Finland showing that 63.8% of women born in Somalia were overweight/obese compared to 29.7% of Finnish women [30]. One study found an association between obesity (but not overweight) and higher risk for giving birth to a baby small for gestational age (RR 2.66, CI 2.01, 3.52) [31] but other studies have shown inconsistent results of the link between overweight and SGA [32]. Another possible explanation is that placenta-mediated diseases (like preeclampsia and SGA) and epigenetic factors can be transferred to the following generations [33].…”
Section: Discussionsupporting
confidence: 80%
“…Maternal demographic characteristics, such as maternal age, pre-pregnancy BMI, parity and maternal education, were associated with birth weight and the risk of SGA infants. A number of epidemiological studies demonstrated that advanced maternal age, primiparity and low BMI before pregnancy elevated the risks of SGA and low birth weight infants [21][22][23] . Several reports indicated that the risk of SGA was higher in low educational subjects compared with high educational subjects 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The birth cohort included 13,801 pregnant women who received antenatal care and delivery in the first affiliated Hospital of Anhui Medical University from January 2011 to December 2014 43 . The diagnosis of ICP was based on the presence of pruritus in combination with elevated serum levels of total bile acid (TBA ≥ 10 μmol/L).…”
Section: Participantsmentioning
confidence: 99%